The artificial intelligence and design of experiment assisted in the development of progesterone-loaded solid-lipid nanoparticles for transdermal drug delivery - Phuvamin Suriyaamporn; Boonnada Pamornpathomkul; Pawaris Wongprayoon; Theerasak Rojanarata; Tanasait Ngawhirunpat; Praneet Opanasopit (Pensoft Publishers, 2024)
The application of Artificial Intelligence (AI) has the potential to revolutionize the formulation development of nanomedicine. This study investigated the physicochemical characteristics of progesterone-loaded solid-lipid nanoparticles (PG-SLNs) produced through an emulsification-ultrasonication process, with a focus on demonstrating the efficacy of this controlled preparation method via the Design of Experiments (DoE) and Artificial Neural Networks (ANN). Critical quality factors, including stearic acid, medium chain triglycerides (MCT), Pluronic F-127, and the amount of propylene glycol (PG), were explored using DoE to streamline experimental setups. The concentration of stearic acid was identified as a crucial factor influencing PG-SLN physicochemical properties, impacting particle size (PS), polydispersity index (PDI), zeta potential (ZP), and %drug loading (%DL). Optimal conditions for PS, PDI, ZP, and %DL were identified. DoE revealed acceptable values across multiple runs, and the ANN model demonstrates high prediction accuracy, surpassing Response Surface Methodology (RSM). The selected PG-SLN formulation was tested for transdermal drug delivery, showing improved permeation compared to PG suspension. Loading with limonene further enhances transdermal drug delivery, attributed to limonene's role as a penetration enhancer. Moreover, the selected PG-SLN formulation was found to be safe and non-toxic to neuronal cells. The combination of DoE and ANN was proposed to enhance predictive ability. This research highlights the potential of PG-SLNs in transdermal drug delivery, emphasizing the role of limonene as a safe and effective enhancer. The study contributes to the growing interest in applying AI tools in pharmaceutical and biomedical fields for improved predictive modeling.